Helical and skyrmion lattice phases in three-dimensional chiral magnets: Effect of anisotropic interactions - J. Chen (Nature Portfolio, 2017)
Abstract In this work, we study the magnetic orders of a classical spin model with anisotropic exchanges and Dzyaloshinskii-Moriya interactions in order to understand the uniaxial stress effect in chiral magnets such as MnSi. Variational zero temperature calculations demonstrate that various helical orders can be developed depending on the interaction anisotropy magnitude, consistent with experimental observations at low temperatures. Furthermore, the uniaxial stress induced creation and annihilation of skyrmions can be also qualitatively reproduced in our Monte Carlo simulations. Our work suggests that the interaction anisotropy tuned by applied uniaxial stress may play an essential role in modulating the magnetic orders in strained chiral magnets.